Measuring performance of universities in fragile countries using analytic hierarchy process - Islam, Rafikul; Mohamed, Shafie Sharif (Creative Decisions Foundations, 2018)
Performance measurement is a process of comparing what transpired with what was planned. Performance measurement assists users to know where they are making progress, where they are slowing down and where they are moving. Due to increasing global competition, both public and private institutions regularly measure their performance levels based on organisational vision and mission. While there are established models to measure performance of universities in developed and developing countries, no such model exist for the universities belonging to fragile countries. This article aims at developing a model based upon AHP to measure performance of universities in fragile countries.